2018
DOI: 10.1016/j.celrep.2017.12.092
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Senescence Is Induced by the Environmental Neurotoxin Paraquat and Contributes to Neuropathology Linked to Parkinson’s Disease

Abstract: SUMMARYExposure to the herbicide paraquat (PQ) is associated with an increased risk of idiopathic Parkinson’s disease (PD). Therapies based on PQ’s presumed mechanisms of action have not, however, yielded effective disease therapies. Cellular senescence is an anticancer mechanism that arrests proliferation of replication-competent cells and results in a pro-inflammatory senescence-associated secretory phenotype (SASP) capable of damaging neighboring tissues. Here, we demonstrate that senescent cell markers are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
363
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 398 publications
(379 citation statements)
references
References 56 publications
13
363
0
3
Order By: Relevance
“…Conversely, DAergic neurotoxins, aging, inflammation, stress and chronic exposure to certain toxins or drugs decrease the generation of new neurons (Chandel et al, ; Das, Gangwal, Damre, Sangamwar, & Sharma, ; Hain et al, ; Iwata et al, ; Klein et al, ; L'Episcopo et al, , , ; Marchetti & Pluchino, ; van Praag et al, ; Seib & Martin‐Villalba, ; Sung, ; Veena et al, ; Villeda et al, ). NSCs are extremely vulnerable to a wide range of insults and toxic exposures, such as the neurotoxicants used in experimental models of basal ganglia injury (Cintha et al, ; He et al, ; He, Uetsuka, & Nakayama, ; L'Episcopo et al, ; Shibui et al, ). Remarkably, exposure to the herbicide paraquat, which is associated with an increased risk of idiopathic PD, results in a pro‐inflammatory senescence‐associated secretory phenotype capable of damaging neuronal, glial and NSC cells, and therefore likely contributing to DAergic neurodegeneration (Chinta et al, ).…”
Section: Wnt/β‐catenin Signalling In Pdmentioning
confidence: 99%
“…Conversely, DAergic neurotoxins, aging, inflammation, stress and chronic exposure to certain toxins or drugs decrease the generation of new neurons (Chandel et al, ; Das, Gangwal, Damre, Sangamwar, & Sharma, ; Hain et al, ; Iwata et al, ; Klein et al, ; L'Episcopo et al, , , ; Marchetti & Pluchino, ; van Praag et al, ; Seib & Martin‐Villalba, ; Sung, ; Veena et al, ; Villeda et al, ). NSCs are extremely vulnerable to a wide range of insults and toxic exposures, such as the neurotoxicants used in experimental models of basal ganglia injury (Cintha et al, ; He et al, ; He, Uetsuka, & Nakayama, ; L'Episcopo et al, ; Shibui et al, ). Remarkably, exposure to the herbicide paraquat, which is associated with an increased risk of idiopathic PD, results in a pro‐inflammatory senescence‐associated secretory phenotype capable of damaging neuronal, glial and NSC cells, and therefore likely contributing to DAergic neurodegeneration (Chinta et al, ).…”
Section: Wnt/β‐catenin Signalling In Pdmentioning
confidence: 99%
“…It is therefore possible that cell senescence contributes to its pathophysiology. In a recent article in Cell Reports , Chinta and colleagues have shown that astrocytes exhibiting an age‐associated (senescent) phenotype are toxic to neurons in vitro, and their removal is associated with better outcomes in a mouse model of PD. This finding may be relevant to other neurodegenerative conditions, such as Alzheimer's and amyotrophic lateral sclerosis, in which cellular senescence is also implicated …”
mentioning
confidence: 99%
“…In postmortem tissue from the substantia nigra of 5 PD patients and 5 controls, Chinta and colleagues show that PD astrocytes have higher expression of senescence markers and elevated levels of inflammatory cytokines and metalloproteinases associated with a senescence‐associated “secretory” phenotype. In human cell culture models, astrocytes and fibroblasts show a more senescent phenotype when exposed to paraquat, a herbicide associated with PD risk, and this is associated with the production of factors, including IL‐6, which are toxic to dopaminergic neurons.…”
mentioning
confidence: 99%
See 2 more Smart Citations